Accumulation of the Type IV prepilin triggers degradation of SecY and YidC and inhibits synthesis of Photosystem II proteins in the cyanobacterium Synechocystis PCC 6803 - Linhartová, Markéta; Bučinská, Lenka; Halada, Petr; Ječmen, Tomáš; Setlík, Jiří; Komenda, Josef; Sobotka, Roman (Molecular microbiology, 2014)
Type IV pilins are bacterial proteins that are small in size but have a broad range of functions, including motility, transformation competence and secretion. Although pilins vary in sequence, they possess a characteristic signal peptide that has to be removed by the prepilin peptidase PilD during pilin maturation. We generated a pilD (slr1120) null mutant of the cyanobacterium Synechocystis 6803 that accumulates an unprocessed form of the major pilin PilA1 (pPilA1) and its non-glycosylated derivative (NpPilA1). Notably, the pilD strain had aberrant membrane ultrastructure and did not grow photoautotrophically because the synthesis of Photosystem II subunits was abolished. However, other membrane components such as Photosystem I and ATP synthase were synthesized at levels comparable to the control strain. Proliferation of the pilD strain was rescued by elimination of the pilA1 gene, demonstrating that PilA1 prepilin inhibited the synthesis of Photosystem II. Furthermore, NpPilA1 co-immunoprecipitated with the SecY translocase and the YidC insertase, and both of these essential translocon components were degraded in the mutant. We propose that unprocessed prepilins inactivate an identical pool of translocons that function in the synthesis of both pilins and the core subunits of Photosystem II.
Keywords: mutace; regulace genové exprese u bakterií; bakteriální proteiny; proteiny fimbrií; endopeptidasy; fotosystém II (proteinový komplex); Bacterial Proteins; Gene Expression Regulation, Bacterial; bakteriální fimbrie; Endopeptidases; Fimbriae, Bacterial; Synechocystis; Photosystem II Protein Complex; Mutation; Glycosylation; glykosylace; Fimbriae Proteins